DIGITALISASI PEMASARAN UMKM KULINER OLAHAN KACANG BEANTIEN TANJUNGPINANG MELALUI SISTEM INFORMASI PENJUALAN BERBASIS WEBSITE - Saputra, Danandjaya; Setiawan, Hendi; Suyanto, Suyanto; Audrik, Audrik (Gapenas Publisher, 2025)
BeanTien Culinary Business is an MSME engaged in the production and sale of processed nut-based products in Tanjungpinang. In its operations, the partner faces several main obstacles, namely the absence of a sales transaction recording system either manually or digitally, difficulty in calculating profits and losses accurately, and limitations in monitoring daily sales developments. This condition impacts the partner's inability to make data-based business decisions and hinders business growth. This community service activity aims to address these problems through the development and implementation of a website-based sales information system. The activity implementation method includes seven stages: partner identification and initial coordination, data collection through interviews and observations, system design using UML modeling, system development with Agile methodology and PHP programming language, system testing using Black Box Testing method, implementation and intensive training for partners, and continuous monitoring and evaluation. The results show that the system was successfully implemented and can be operated properly by the partner. The system is able to store transaction data in a structured manner, generate sales reports based on specific periods, and export reports to Excel and PDF formats. Through intensive training and mentoring, partners are able to operate the system independently and experience tangible benefits in the form of improved recording efficiency, ease of sales monitoring, and accuracy in calculating profits and losses. This activity successfully increased the partner's digital literacy capacity and supported the digital transformation of MSMEs in Tanjungpinang.